ANALISA PENGARUH AKTIVITAS PEMASARAN MEDIA SOSIAL TERHADAP PURCHASE INTENTION YANG DIMEDIASIKAN TRUST DAN BRAND IMAGE - Edy Yulianto Putra; Hepy Hefri Ariyanto; Meliana Meliana (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
The research in this article aims to analyze the influence of entertainment, interaction, and trendiness on customer purchase intentions in social media marketing content which is mediated by trust and brand image. The method used in this research is a quantitative method with purposive sampling technique. This research uses primary data, namely data obtained by distributing questionnaires via Google Form to 318 respondents with 27 questions. This research data was processed using the PLS-SEM program. The results of this research are that entertainment, interaction, and trendiness have a positive effect on trust and brand image. Trust and brand image also have a significant influence on Purchase Intention. Apart from that, there is a significant relationship between Entertainment, Interaction, and Trendiness on Purchase Intention which is mediated by Trust and Brand Image, so it can be concluded that marketing activities carried out on social media through content can grow customer purchase intentions. Therefore, companies or businesses can be more active in cyberspace to carry out their marketing and advertising programs with social media platforms through more interesting marketing content.